ChemInform Abstract: Alkene Isomerization—Hydroboration Promoted by Phosphine‐Ligated Cobalt Catalysts. Issue 41 (October 2015) - Scheuermann, Margaret L.; Johnson, Elizabeth J.; Chirik, Paul J.
Abstract The catalyst is found to effectively promote the boron incorporation with nonterminal selectivity and adjacent to π‐systems even in substrates where the alkene is at a remote position.